Elucidating the role of SORL1 as an APOE receptor using iPSC‐derived astrocytes: Molecular and cell biology/stem cells, iPS cells. (7th December 2020) - Lee, Hyo; Pan, Cheryl; Goberdhan, Sri; Young, Jessica E.; Young‐Pearse, Tracy
Abstract: Background: Apolipoprotein E (APOE), the strongest genetic risk factor in late‐onset AD (LOAD), encodes a protein that can interact with Aβ and regulate its clearance. Interestingly, SORL1, another AD risk gene, belongs to the family of APOE receptors involved in Aβ clearance. SORL1 is the only APOE receptor gene that has been identified as a genetic risk factor in LOAD. Recent studies identified SORL1 loss‐of‐function variants in familial AD patients, suggesting that SORL1 may be a causal gene for AD. Here, we investigated the potential convergent mechanisms of APOE and SORL1 function in the brain by examining the novel function of SORL1 in human astrocytes in Aβ clearance. Method: iPSC‐derived astrocytes were generated from individuals with 1) different APOE isoforms 2) SORL1 knock out (KO), risk SNPs and missense mutations and 3) other AD risk SNPs using two astrocyte differentiation protocols. Aβ clearance assays were performed by treating the astrocytes with synthetic or cell derived Aβ, then monitoring the Aβ level in both media and lysate over time to determine the ability of astrocytes to uptake and clear Aβ. Result: We have generated iPSC‐derived astrocytes from multiple lines to characterize whether SORL1 functions as an APOE receptor in human astrocytes. We determined that SORL1 is highly expressed in astrocytes, both in cytoplasmic and cell surface compartments, and SORL1 can interact with APOE in iPSCs as shown by co‐immunoprecipitation. Further, our preliminary data show that SORL1 KO astrocytes show elevated endogenous extracellular Aβ levels, and impaired Aβ clearance ability when treated with exogenous or cell derived Aβ. Lastly, when Aβ uptake was examined using APOE isogenic astrocytes, APOE KO show impaired clearance, supporting a role for endogenously secreted APOE in Aβ uptake in human astrocytes. Ongoing studies are interrogating the contribution of SORL1 in APOE‐mediated Aβ clearance. Conclusion: Here, I have utilized iPSC‐derived astrocytes to examine the novel role of SORL1 as an APOE receptor in astrocytes, and investigate a potential convergent mechanism that APOE and SORL1 play in Aβ clearance.